PENINGKATKAN KECAKAPAN PARTISIPATIF PEMILIH PEMULA PEMILU DI NEGERI HUKURILA KOTA AMBON - Jusuf Leiwakabessy; Ronald Darlly Hukubun; Vica Jillyan Edsti Saija; Maya Lisa Haupea; Masnia Masnia (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The community service is carried out to provide knowledge to the young people of Negeri Hukurila, South Leitimur District, who are first-time voters. First-time voters, according to the Election Law, refer to individuals aged 17 and above or those who have been married. First-time voters are those who are eligible to vote for the first time in any type of election, including general elections, presidential elections, legislative elections, or other elections. They can be aged 17-18 or older and have met the voter requirements set by the laws of their country or jurisdiction of residence. The purpose of this community service is to increase the participation of first-time voters, especially the young people of Negeri Hukurila who have just graduated from high school or vocational school. Based on observations, it has been found that the youth in Negeri Hukurila have low political participation in elections, and they also have limited information about elections and a lack of political education. With reference to these issues, we conducted community service with the hope that after the socialization on increasing the participation of informed first-time voters, their knowledge about elections and politics would increase, thereby impacting the high level of participation of first-time voters in the upcoming 2024 elections.